Crimes in the nuclear family Crimes against women (2012)
This article seeks to identify and examine irregular sexual behavior such as rape presented in the Province of Tunja between the years of 1800 - 1820, and how they were punished, from existing native laws for the time. For this purpose it was necessary to further read and analyze claims documents found in the historical archives of the region of Boyacá (Historical Background) of Tunja